Agricultural Land Intensification Practices in Nawalparasi District (West) - Dhakal, Bhola Nath (Humanities and Social Sciences Journal, 2022)
Land intensification is the process whereby land use activity is delicate through increasing yield per unit area and by crop intensification. The present study has examined the agricultural land intensification practices in different parts of Nawalparasi District. This study has used primary and secondary data. Primary data has been produced from household survey, focus group discussion, and key informant interview and field observation. Furthermore, published and unpublished reports such as profiles, annual progress reports, research articles, maps and images have been used to create secondary data. It is observed that farmers have practiced to cultivate many crops than the past to increase production even in the same area of land, changing crop and varieties within the particular crop and priority has been given to market oriented production of agricultural commodities like vegetables, livestock rising and diary product, poultry farming, and bee-keeping activities.